The Charter of the Kwidzyn (Marienwerder) Convivium Musicum of 1587 as a source for the history of musical culture in Prussian towns - Bogdan, Izabela (Interdisciplinary Studies in Musicology, 2018)
Music societies, referred to in German documents as ‘Kantoreigesellschaften’, ‘Musikgesellschaften’ or ‘Musikkranzlein’, and in Latin records as ‘collegia musica’ or ‘convivia musica’, were founded in numerous towns in German-speaking territories during the veiy first years after the Reformation. They were of an elite character, comprising the most prominent burghers, including the mayor, aldermen, councillors, church officials (pastor, deacon, cantor, organist) and local schoolteachers. Pupils and students attending Protestant schools and universities in German-speaking regions also actively participated in musical performances given by the societies. Their members provided a polyphonic setting for the Mass and other services, as the convivia had the noble mission of singing to the glory of God and educating young people. There are few extant charters of sixteenth-century societies of this type. The present article provides a detailed description of the charter of the Convivium Musicum in Kwidzyn, a town located during the sixteenth century and the first half of the seventeenth century within the borders of Ducal Prussia. This society, founded on 18 February 1587, followed an early modem trend for creating music societies under the patronage of municipal councils and the Church. Its initiator was a local Protestant superintendent (‘Erzpriester’) and pastor, Salomon Klein, supported by deacons, a local teacher, an organist, mayors, aldermen, a notary, a municipal judge, town councillors and others. The article carefully examines each chapter of the charter, providing information on the Convivium’s structure, organisation and activities and the duties of its members.